Potency of (Poly) Acrylic/Carboxymethyl Starch-Chitosan Biohydrogel for Curcumin Oral Delivery Matrix - Ruriani, Eka; Mangunwidjaja, Djumali; Richana, Nur; Sunarti, Titi Candra (Pharmaceutical Sciences and Research, 2018)
Biohydrogel has gathered great interest in the pharmaceuticals field. This natural polymers were biodegradable, non-toxic, biocompatible, and its specific ability to response environment change can be considered for the controlled released matric of bioactive compound. In this study, the biohydrogel was synthesized by graft-copolymerization of acrylic acid onto carboxymethyl starch (CMS) and chitosan. The objective of this research was to determine the effect of CMS-chitosan ratio on the biohydrogel characteristic. The acrylic acid was grafted on to the backbone (3:1) using cerric ammonium nitrate as the inisiator.A standarded curcumin was applied to test the binding potency of matrix. A higher CMS ratio in the polymer mixture (4:1) revealed the highest swelling power (16.9 w/w) and percentage of curcumin absorption (17.34%). All samples have pH-responsive swelling properties, with the swelling trend was observed in the order of distilled water >HCl solution > phosphate buffer solution. FTIR spectra and SEM micrographs has confirmed the graft-copolymerization of PAA/CMSCs biohydrogel by describing the appearance of peak around 1600 cm-1and the morphology of granular structure, respectively. The graft-copolymerization of acrylic acid onto the two anionic natural polymer by cerric ammonium nitrate as the initiator has resulted a pH-dependent swelling biohydrogel, and it has the ability to deliver curcumin in stomach-targeted system.